IMPLEMENTASI METODE EXTREME PROGRAMMING PADA SISTEM INFORMASI LAYANAN INSPEKSI KENDARAAN UNTUK JUAL BELI MOBIL BEKAS BERBASIS WEBSITE DI PT. FHADIRA INOVASI TEKNOLOGI - Rayhan Fauzan; Ari Syaripudin (CV. Multi Kreasi Media, 2023)
PT FHADIRA INOVASI TEKNOLOGI or commonly known as PT Fitek is a company engaged in the field of vehicle inspection and buying and selling of vehicles, but in reality based on what currently exists PT Fitek has not fully implemented technological developments, because at this time consumers who want their vehicles Inspection is still done manually, namely still using a booking order using WhatsApp, in a manual way like this based on the results of an interview with one of the PT Fitek parties, many problems were found, namely frequent clashing inspection schedules and this caused another problem, namely when making reports it takes a lot of time because you have to manually record orders. Then PT Fitek also doesn't have a website for buying and selling cars that have been inspected, so to see the vehicles offered, consumers still have to come to the location to buy cars that have been inspected. In making this system using the Extreme Programming method. The system created is based on the codeigniter framework with the mysql database. The results of this study have created a special website-based system for buying and selling used cars at PT. FHADIRA TECHNOLOGY INNOVATION.